Determinants of financial information disclosure: A visualization test by cognitive mapping technique - Nassreddine Garoui (Journal of Economics, Finance and Administrative Science, 2016)
The purpose of this paper is to examine determinants of financial information disclosure by Tunisian companies. The methodology is based on qualitative approach, using the cognitive mapping technique. To take into account the specificities of the Tunisian economic, we felt that it is essential to conduct a qualitative analysis in the light of which we can identify the factors motivating the disclosure of financial information. The qualitative analysis is based on the census via a set of cases carried out in several Tunisian companies to understand their perceptions regarding the determinants of financial disclosure. – – El objetivo de este artículo es examinar los determinantes de la divulgación de la información financiera por parte de empresas tunecinas. La metodología se basa en un enfoque cualitativo mediante la técnica de mapas cognitivos. Si se quiere tener en cuenta las particularidades de la economía de Túnez, es esencial llevar a cabo un análisis con el que sea posible identificar los factores que motivan la divulgación de la información financiera. El análisis cualitativo se basa en el censo con una serie de casos dirigidos en varias empresas tunecinas para comprender sus percepciones con respecto a los determinantes de la divulgación de la información financiera.
Keywords: M40; 330; Disclosure information; Financial information; Cognitive mapping; Divulgación de la información; Información financiera; Mapas cognitivos